IMPLEMENTASI PENCATATAN BIAYA LINGKUNGAN (ENVIRONMENTAL ACCOUNTING) DAN PENINGKATAN KESADARAN SISWA TERHADAP AKUNTANSI BERKELANJUTAN MELALUI PENGELOLAAN SAMPAH SEKOLAH - Ingga Mualana; Iroh Rahmawati; Eko Pujiyono (Ensiklopedia Research and Community Service Review, 2026)
This community service initiative aims to analyze the implementation of environmental cost recording in school waste management, assess students' awareness of sustainability accounting, and develop an environmental accounting-based learning model. The activity was conducted at SMAN 1 Kramatwatu using a descriptive-qualitative approach supported by quantitative data gathered through observation, interviews, documentation, and questionnaires. The results indicate that environmental cost recording has not yet been carried out systematically and remains bundled with general school operational costs. Student awareness regarding sustainability falls into the moderate category. Based on these findings, a waste management-based learning model was developed, integrating environmental cost recording through Project-Based Learning and Contextual Teaching and Learning approaches. This model proved effective in enhancing students' understanding of accounting and environmental awareness in a more contextual and practical manner.Keywords: environmental accounting, environmental costs, waste management, sustainability accounting.